2021
DOI: 10.1080/13607863.2021.1950618
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among older adults with symptoms of cognitive decline consulting specialist health care

Abstract: Objectives: To explore alcohol consumption among older Norwegian adults with symptoms of cognitive decline, assess the agreement between the reports of older adults and their next of kin regarding a person's alcohol consumption, and explore clinical and sociodemographic variables associated with agreement. Method: Alcohol consumption was measured among 3608 older adults consulting specialist health care for symptoms of cognitive decline. Agreement between the participant and their next of kin regarding the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Alcohol consumption [54] Single question assessing alcohol consumption frequency on an 8-point scale. The next of kin's response was selected for analysis, as previous work has indicated that the next of kin may be the most valid source of this information [55]. The question, "About how often in the last 12 months did you drink alcohol,"?…”
Section: Measurement Descriptionmentioning
confidence: 99%
“…Alcohol consumption [54] Single question assessing alcohol consumption frequency on an 8-point scale. The next of kin's response was selected for analysis, as previous work has indicated that the next of kin may be the most valid source of this information [55]. The question, "About how often in the last 12 months did you drink alcohol,"?…”
Section: Measurement Descriptionmentioning
confidence: 99%